2014
DOI: 10.1371/journal.pone.0083526
|View full text |Cite
|
Sign up to set email alerts
|

Potential Cost-Effectiveness of a New Infant Tuberculosis Vaccine in South Africa - Implications for Clinical Trials: A Decision Analysis

Abstract: Novel tuberculosis vaccines are in varying stages of pre-clinical and clinical development. This study seeks to estimate the potential cost-effectiveness of a BCG booster vaccine, while accounting for costs of large-scale clinical trials, using the MVA85A vaccine as a case study for estimating potential costs. We conducted a decision analysis from the societal perspective, using a 10-year time frame and a 3% discount rate. We predicted active tuberculosis cases and tuberculosis-related costs for a hypothetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 38 publications
2
36
0
1
Order By: Relevance
“…This result is consistent with a recently published study by Ditkowsky and Swartzman which showed that, at values below 40% efficacy for MVA85A, the MVA85A booster strategy is more expensive and only slightly more effective than BCG alone [40]. They are also similar to earlier analyses of novel vaccines for TB [41,42].…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with a recently published study by Ditkowsky and Swartzman which showed that, at values below 40% efficacy for MVA85A, the MVA85A booster strategy is more expensive and only slightly more effective than BCG alone [40]. They are also similar to earlier analyses of novel vaccines for TB [41,42].…”
Section: Discussionsupporting
confidence: 91%
“…The included studies comprised 18 deterministic, compartmental, dynamic models constructed using difference or differential equations, 4,10-14,16-21,23-25,27-29 3 Markov decision tree analyses, 15,22,31 one a simple mathematical model including a fixed number of transmissions per case, 30 and one statistical model 26 . A subset of these papers (n = 5) present analytical solutions of models and discuss the theoretical implications of a range of factors on the impact of vaccines 11,13,17,25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…An anticipated vaccine efficacy in the range of 40–80% was most commonly modeled, 10,12,15,18,20-22,27-31 though some explored the public health impact of the extremes above 15,20,29 or below 10,12,22,29 this range. Vaccine efficacy was modeled as ‘take’ (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Such analyses of future vaccines have been undertaken for several other diseases (13)(14)(15)(16)(17) but have been limited to exploring the costeffectiveness of infant vaccination in Asia and Sub-Saharan Africa for TB (18)(19)(20). To inform the products and targeting that will be most useful for achieving the 2050 elimination target (3), there is a need to systematically estimate the impact in a wide range of settings of a variety of potential TB vaccine profiles defined by efficacy, duration of protection, and potential target groups (e.g., by age).…”
mentioning
confidence: 99%